2000
DOI: 10.1016/s0014-5793(00)01942-6
|View full text |Cite
|
Sign up to set email alerts
|

C2PA, a new protein expressed during mouse spermatogenesis

Abstract: C2PA is a novel protein that contains a C2 membrane binding domain, a PDZ protein/protein interaction domain, and an ATP/GTP binding domain. C2PA is expressed during embryogenesis from 8.5 days post-coitum (dpc) until birth. After birth, C2PA expression is mainly observed in the post-natal and adult testis. During spermatogenesis, C2PA transcripts are specifically observed in the spermatocytes, whereas spermatogonia and spermatids are negative. Taken together, these results suggest that C2PA might be involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
1
10
1
Order By: Relevance
“…Furthermore, because C2PA-RGS3, PDZ-RGS3, and C2PA share eight coding exons, RNA probes originally designed to detect mRNAs encoding mouse PDZ-RGS3 or mouse C2PA may have inadvertently detected transcripts arising from two or three other mRNAs. The probe used to detect transcripts that encode PDZ-RGS3, nucleotides 3-861 of the mouse PDZ-RGS3 cDNA, contained shared nucleotide sequence with other isoforms, and the probes used for northern blot to detect transcripts that encode C2PA (nucleotides 818-2068) and in situ hybridization (nucleotides 818-4712) both overlapped the coding regions for mouse C2PA-RGS3 and PDZ-RGS3 [16,17]. Also, the mRNAs that encode C2PA and PDZ-RGS3 are similar in size making their distinction on northern blot difficult unless specific probes are used.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, because C2PA-RGS3, PDZ-RGS3, and C2PA share eight coding exons, RNA probes originally designed to detect mRNAs encoding mouse PDZ-RGS3 or mouse C2PA may have inadvertently detected transcripts arising from two or three other mRNAs. The probe used to detect transcripts that encode PDZ-RGS3, nucleotides 3-861 of the mouse PDZ-RGS3 cDNA, contained shared nucleotide sequence with other isoforms, and the probes used for northern blot to detect transcripts that encode C2PA (nucleotides 818-2068) and in situ hybridization (nucleotides 818-4712) both overlapped the coding regions for mouse C2PA-RGS3 and PDZ-RGS3 [16,17]. Also, the mRNAs that encode C2PA and PDZ-RGS3 are similar in size making their distinction on northern blot difficult unless specific probes are used.…”
Section: Discussionmentioning
confidence: 99%
“…A direct comparison of the AK004648 nucleotide sequence and the nucleotide sequence that encodes PDZ-RGS3 indicates that AK004648 is a partial cDNA sequence for the PDZ-RGS3 isoform (there are some minor disagreements between the two sequences). A TBLASTN search of the NCBI nonredundant database with the N-terminal 398 amino acids of mouse PDZ-RGS3 revealed that a portion aligned with the coding region for a previously reported open reading frame termed C2PA [17] and the predicted coding region of a human cDNA. Another TBLASTN search with the N-terminal 398 amino acids of mouse PDZ-RGS3 using the NCBI human genome database revealed partial identity with a cluster of likely exons that overlapped the identified exons from which the human C2PA cDNA arose, which just happened to lie 40 kb away from the previously identified RGS3 cluster of exons on chromosome 9.…”
Section: The Identification Of Human Pdz-rgs3mentioning
confidence: 99%
See 2 more Smart Citations
“…SRB-RGS bears a PDZ domain that is a multi-functional proteinprotein interaction module that plays important roles in organizing signal transduction complexes, clustering membrane proteins, and maintaining cell polarity at the NH 2 -terminal, as well. 16,17) rERaC/D interacted in vitro with partial SRB-RGS1-495 amino acid (a.a.). SRB-RGS suppressed the transcriptional activities of ERa and the other promoters.…”
mentioning
confidence: 99%